Kompendium Arsitektur Tempat Tinggal Yang Nyaman Dan Hemat Biaya Untuk Mahasiswa Indonesia di Nagoya, Jepang - Edar, Ahmad Nadhil; Bima, Muhammad Irfan Maulana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Indonesian students in Nagoya often face the challenge of finding a place to live that is comfortable, cost effective, and appropriate to their culture and needs. To address this issue, the Universitas Muslim Indonesia PKM team is working with PPI Nagoya partners in Japan to organize an international PKM activity focusing on design guidance and cost management of student housing. This activity will combine presentation, discussion, workshop, and mentoring methods to provide material on architectural design concepts that suit the culture and needs of students, optimization of space utilization, selection of environmentally friendly building materials, and architectural principles to improve comfort. In addition, students will receive training on cost-effective architectural principles, budget management strategies, life-cycle cost analysis, and construction/renovation cost management. In addition to providing materials, the PKM team will also assist students in designing or selecting a home that meets their needs. Monitoring and evaluation of the implementation of the solutions provided will also be conducted to ensure the effectiveness of the program. As a final result, guidelines and modules in printed or digital form will be compiled for dissemination and help more Indonesian students in Nagoya to find an ideal place to live. This international PKM activity is expected to provide practical and useful solutions for Indonesian students in Nagoya, improve the quality of their residence, and build closer relationships and cooperation between students and PPI Nagoya.